Ohmic Heating Effect of Viscoelastic Dielectric Liquid over a Slanted Stretching Sheet - Veena N (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research explores the Ohmic heating phenomenon in a dielectric liquid flowing over an inclined, stretching sheet. It also highlights the significance of the permeability parameter in heat transfer. The fundamental governing equations undergo a transformation into ordinary differential equations (ODEs) by applying a similarity transformation. This approach simplifies the problem by reducing the number of independent variables, making the equations more manageable for analytical or numerical solution. To obtain the numerical solution, the well-established Runge-Kutta-Fehlberg method combined with the shooting technique is employed. The study examines the impact of various key parameters on fluid flow and heat transfer, with results presented graphically. Additionally, numerical values of skin friction and the Nusselt number are provided in a table for different parameter variations.